The role of the indigenous breeds for beef production in Southern Africa - Maule, J.P. (1973)
Production performance of indigenous beef breeds of southern Africa were investigated. Discussions and data on calving rate, calf mortality, weaning and birth weights, adult live weights, carcass yield, and feed conversion efficiency; in comparison to crossbreds of Friesian and Hereford cattle included.